Is AI a subject that can live together with humans? - Kwon, Young Woo (AI & society, 2025)
This article explores whether AI can be a human-like subject that can live together with humans. I argue that living together is conceptually different from being together or coexistence and symbiosis in an ecosystem. I propose three conditions for living together and consider as subjects only those beings that can live together in a cultural and inter-subjective way. And I try to define the subject as a being which can build its relationships with the world in three ways. Then the conditions of living together will be combined with the concept of subject. The first condition is that the subject should be conscious of its relationship with others. The second condition is that the subject should form reciprocal relationships with others. The third condition is that the subjects should have the same representation of the relationship with others. This article attempts to examine whether AI can fulfill the three conditions of living together. Although AI seems to be able to think, express, act, feel, even be conscious and so on, it is very unlikely that AI can build the same world as the human world. Therefore, even if we cannot discern ourselves from AI, we humans can never enter its world and vice versa. The reason is very simple: humans are ontically different from AI. In society, humans and AI can be together, but they cannot live together. Even if AI could eventually have a consciousness, genuine social living together between humans and AI is impossible. We humans can recognize AI as a pseudo-subject. Nevertheless, such a subject is not one that can live together with humans. Even if AI were conscious and could pretend to be a human-like subject, it could not be a genuine subject unless it could live together with humans. Many people warn that AI could be dangerous to humans. These so-called threats might not come from AI itself, but from humans themselves.